Risk factor of postoperative adverse events among children with duplex kidney undergoing upper pole heminephrectomy: a single-center experience - Wang, Denghui; Cui, Mengjie; Chu, Xiangyang; Han, Xiaojiang; Liu, Pengpeng; Zhao, Xiang; Fan, Yingzhong (Frontiers in Pediatrics, 2024)
The aim of this study was to identify the risk factors for postoperative adverse events in children with duplex kidney undergoing upper pole heminephrectomy.We collected clinical data from pediatric patients with duplex kidney who underwent upper pole heminephrectomy. Based on the presence or absence of postoperative adverse events, the patients were divided into two groups: an adverse events group (n=16) and a non-adverse events group (n=37), using multivariate logistic regression analysis to screen for independent risk factors for postoperative adverse events.Through univariate and multivariate analysis, we found that the presence of upper renal ureterocele (P=0.042, OR=7.116, 95% CI 1.073-47.172), as well as the presence of accessory renal artery type (P=0.016, OR=10.639, 95% CI 1.551-72.978) and other types (P=0.039, OR=3.644, 95% CI 0.351-37.836) as the upper kidney's blood supply artery increase the risk of postoperative adverse events, with these differences being statistically significant.In pediatric patients with duplex kidney undergoing upper pole heminephrectomy, the presence of upper renal ureterocele and the presence of accessory renal artery type and other types as the upper kidney's blood supply artery are independent risk factors for postoperative adverse events.